ArhGEF18 regulates RhoA-Rock2 signaling to maintain neuro-epithelial apico-basal polarity and proliferation - Herder, Cathrin; Loosli, Claudia; Wittbrodt, Joachim (Development, 2013)
The vertebrate central nervous system develops from an epithelium where cells are polarized along the apicobasal axis. Loss of this polarity results in abnormal organ architecture, morphology and proliferation. We found that mutations of the guanine nucleotide exchange factor ArhGEF18 affect apicobasal polarity of the retinal neuroepithelium in medaka fish. We show that ArhGEF18 -mediated activation of the small GTPase RhoA is required to maintain apicobasal polarity at the onset of retinal differentiation and to control the ratio of neurogenic to proliferative cell divisions. RhoA signals through Rock2 to regulate apicobasal polarity, tight junction localization and the cortical actin cytoskeleton. The human ArhGEF18 homologue can rescue the mutant phenotype, suggesting a conserved function in vertebrate neuroepithelia. Our analysis identifies ArhGEF18 as a key regulator of tissue architecture and function, controlling apicobasal polarity and proliferation through RhoA activation. We thus identify the control of neuroepithelial apicobasal polarity as a novel role for RhoA signaling in vertebrate development.